STRATEGI PENERAPAN BUDAYA BELAJAR BERKEADABAN DI SMPN 22 SURABAYA - Dzikrul Akbar; Abdul Muqit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School culture plays a strategic role in shaping students’ character and social attitudes beyond academic achievement. One important manifestation of school culture is the implementation of a civilized learning culture that emphasizes ethical behavior, respect, and responsibility in daily learning activities. This study aims to analyze the strategies for implementing a civilized learning culture at SMP Negeri 22 Surabaya. The research employs a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving school principals, teachers, and students. The results indicate that the implementation of a civilized learning culture is integrated into classroom learning, school interactions, and daily habituation activities. School culture functions as an effective medium for internalizing values of civility through consistency, role modeling by teachers, and supportive school systems. Despite challenges arising from diverse student backgrounds and external influences, the school maintains the continuity of a civilized learning culture through habituation, exemplary leadership, and collaboration with parents. In conclusion, a civilized learning culture can serve as an effective strategy for character building and the development of students’ social attitudes at the junior high school level.